RTS/CTS Framework Paradigm and WLAN QoS Provisioning Methods - Nj., Mohamed; Sahib, Shahrin; Suryana, Nanna; Hussin, B. (The Science And Information (SAI) Organization Limited, 2017)
Wireless local area network (WLAN) communications performance design and management have evolved a lot to be where they are today. They went through some technology’s amendments and innovations. But, some performance tools remained almost unchanged and play a fundamental role in contemporary networking solutions despite the latest innovations higher influence on their indisputable and important function. That is the case with Request to send (RTS) and consent to receive (CTS) protocols. They are among the former technologies, which helped for transmission control with better performance in WLAN environment. They are so important, particularly since the advent of sensitive data networking (e.g. internet telephony, audio and video materials distribution) over the internet protocol (IP). Up to recent years following today’s multimedia WLAN based networks deployment trends, RTS/CTS) contributed to provide networks with some expected good performance levels prior to the discovery of more sophisticated methods for this purpose (i.e. performance enhancements). And yet, one may question whether the new technologies have rendered RTS/CTS frameworks obsolete; or are they now used only for some specific network applications traffic management? This articles review attempts to comprehensibly study some of the research works, which have had interest in RTS/CTS mechanism as tools for WLAN applications performance support. Various researches have studied these tools from their early innovation as network node’s built-in component, through different frameworks associated with WLAN legacy (IEEE 802.11) MAC protocols. This paper analyzed RTS/CTS initial implementation as mere network performance solution from packets’ collision avoidance perspective; and then for transmission delay due to hidden nodes and their false deployment. The article closes up on a critical analysis on the possible long time contribution of these protocols into integrated schemes based WLAN QoS performance design.